2022
DOI: 10.52131/pjhss.2022.1004.0313
|View full text |Cite
|
Sign up to set email alerts
|

The Framework of Loyalty and Customer Satisfaction with Perceived value and Omni-channel Integration Quality as Drivers in Banking Sector of Pakistan

Abstract: Technological advancement and digitalization bring drastic transformations in the business market. This study intends to recognize the factors that influence customer loyalty and enhance the literature relevant to the evolving topic of Omni-channel which provides a seamless experience to consumers among all channels. This study empirically investigates the association among the Omni-channel “integration quality, perceived value, customer satisfaction & customer loyalty” in the Pakistani banking segment. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Furthermore, (Mishra, 2022) demonstrated that corporate communication, a construct intimately linked to corporate image, directly positively affects customer loyalty. Consequently, constructing a robust corporate image constitutes an essential prerequisite for establishing and preserving customer loyalty within the banking industry (Kanwal et al, 2022;Mariska & Khasanah, 2022). The factors elucidated in the literature engender salient practical implications for banking.…”
Section: Corporate Imagementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, (Mishra, 2022) demonstrated that corporate communication, a construct intimately linked to corporate image, directly positively affects customer loyalty. Consequently, constructing a robust corporate image constitutes an essential prerequisite for establishing and preserving customer loyalty within the banking industry (Kanwal et al, 2022;Mariska & Khasanah, 2022). The factors elucidated in the literature engender salient practical implications for banking.…”
Section: Corporate Imagementioning
confidence: 99%
“…A sizable body of scholarly work has examined various determinants of customer loyalty within the banking sector across diverse international contexts (Abbasi et al, 2011;Albarq, 2023;Kanwal et al, 2022Kanwal et al, )et al, 2022. Key loyalty antecedents elucidated within mainstream academic discourse encompass an array of factors, including but not limited to, perceived service quality, customer satisfaction, corporate image, switching costs, trust and perceived value (Chaudhuri & Holbrook, 2001;Žabkar et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the increased convenience and accessibility, a prevailing challenge is the apparent low level of customer positive affect experience and customer loyalty. This issue poses a critical concern for the sustainability and growth of banks operating in the omnichannel landscape (Kanwal, Arshad, Shahid, & Gul, 2022). Numerous indicators point to low customer loyalty and customer'positive experience in the omnichannel banking sector (Mainardes, de Moura Rosa, & Nossa, 2020).…”
Section: Introductionmentioning
confidence: 99%